Soil Health Response of Histosols to Flooded versus Dry-Fallow Conditions during Summer - Jehangir H. Bhadha; Jay Capasso; Abul Rabbany; Nan Xu; Matthew VanWeelden (EDIS)
Evaluating changes in soil properties associated with flooded fields during the summer months in the Everglades Agricultural Area (EAA) provides us an opportunity to assess the effect of soil management associated with flooded versus dry-fallow field conditions on Histosols. This information will be beneficial to current and potential growers farming flooded rice in south Florida, as well as Extension agents who work on rice and soil conservation agencies such as the USDA Natural Resources Conservation Service (NRCS). This new 6-page publication was written by Jehangir H. Bhadha, Jay Capasso, Abul Rabbany, Nan Xu, and Matthew VanWeelden, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss697